Self-employment in UK law - Barnard, Catherine; Georgiou, Despoina (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The United Kingdom has noted a rapid increase in the number of self-employed persons in the last forty years. This has prompted a return to the debate on the regulation of this category of workers. What are the key characteristics of the self-employed? Are they covered by labour law and social security regulations? This chapter answers these questions by looking at the legal framework applicable to the self-employed in the UK. In section 2, the author characterizes the main tendencies regarding self-employed activity in the United Kingdom as presented in a report of the Office of National Statistics for 2020. In sections 3 and 4, she analyses the definition and the legal framework that guarantee protection applicable to the self-employed. The author places particular emphasis on the tri-partite character of the British legal system in individual employment law, which includes certain categories of self-employed in the British definition of worker. Finally, section 5 is devoted to the ever more popular phenomenon of “bogus self-employment” and the legal mechanisms designed to combat it.